Earnings Responses to Social Security Contributions: Evidence from Older Workers in Canada - Adam M. Lavecchia; James Stutely (Institute of Labor Economics (IZA), 2025)
This paper documents sharp bunching in third-party reported employment earnings at a basic exemption for social security contributions among older workers. Beginning in 2012, workers age 60-64 who were receiving a public pension were required to make social security contributions equal to 9.9 percent of their employment earnings above a basic exemption threshold of 3,500. Using administrative data on third-party reported earnings and a differences-in- bunching estimator we document sharp bunching at the 3,500 threshold. We argue that our results represent new evidence on the role of firms in mediating the earnings response to payroll taxes.
Keywords: H20; H24; H25; H31; H32; H55; J22; J23; J38; 330; social security contributions; sharp bunching; employment earnings